Controlling crystallization, phase transformation and magnetic properties of amorphous FeNiP by annealing in nano-confinement. Issue 29 (7th August 2015) - Winkler, N.; Peterlechner, M.; Wilde, G.
<x xml:space="preserve">Abstract</x> The influence of nanometer restricted confinement provides new insight into surface enhanced nucleation and volume diffusion restricted growth of phases.